The Influence of CEO Narcissism and Sustainability Reporting on Tax Avoidance: Exploring Institutional Ownership as a Moderating Variable - Ahmad Muhlis; Mira; Masrullah (Jurnal Manajemen Bisnis, 2024)
The decrease in CEOs' tax avoidance can be attributed to the absence of sustainability activities within the company, which consequently leads to decreased economic stability. In the contemporary business landscape, companies are mandated to provide Sustainability Reporting. This study employed purposive sampling, resulting in a sample of 43 companies selected based on specific criteria. The objective of this research was to examine the impact of CEO Narcissism and Sustainability Reporting on tax avoidance, with institutional ownership serving as a moderating variable listed on the IDX (Indonesia Stock Exchange). The data analysis methods included Descriptive Statistics, Classic Assumption Tests, Multiple Linear Regression Analysis with Moderated Regression Analysis, and hypothesis testing. The findings revealed that: 1) CEO Narcissism showed no significant effect on tax avoidance, 2) Sustainability Reporting had a significant impact on tax avoidance, 3) institutional ownership did not moderate the relationship between CEO Narcissism and Tax Avoidance, and 4) institutional ownership moderated the relationship between Sustainability Reporting and Tax Avoidance.